2014
DOI: 10.1515/geo-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Improved land cover mapping using aerial photographs and satellite images

Abstract: Manual Land Cover Mapping using aerial photographs provides sufficient level of resolution for detailed vegetation or land cover maps. However, in some cases it is not possible to achieve the desired information over large areas, for example from historical data where the quality and amount of available images is definitely lower than from modern data. The use of automated and semiautomated methods offers the means to identify the vegetation cover using remotely sensed data. In this paper automated methods wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…Using the original RGB bands, at least in our study area, resulted a good result with 82% OA, but we have to consider that there can be areas where the accuracy is smaller due to similar land cover categories. Varga et al [117] found that visible range orthophotos provided only 61-68% OA, depending on the given image; in their image forests, vegetation on arable lands and even the water had green tone causing a large amount of misclassification. Cots-Folch et al [118] gained 74% OA with the application of textural information.…”
Section: Discussionmentioning
confidence: 99%
“…Using the original RGB bands, at least in our study area, resulted a good result with 82% OA, but we have to consider that there can be areas where the accuracy is smaller due to similar land cover categories. Varga et al [117] found that visible range orthophotos provided only 61-68% OA, depending on the given image; in their image forests, vegetation on arable lands and even the water had green tone causing a large amount of misclassification. Cots-Folch et al [118] gained 74% OA with the application of textural information.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed maps act as a digital representation of both natural and historical elements and they are now common as a result of data availability (Varga et al 2015, Werle 2016. Within this new context, our approach tries to find a solution for an accurate and precise GIS mapping of the urban medieval site, using UAv photogrammetric techniques to reveal topographic and historical features.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the soil cover map was prepared based on the images' supervised classification procedure, using the Maximum Likelihood algorithm and accuracy was assured by the KIA statistical index (Poznanovic et al, 2014;Calijuri et al, 2015;Varga et al, 2015;Mishra and Rai, 2016). The image used was from Landsat 8, in the bands of the Operational Land Imager (OLI) sensor, dated September 03rd 2017, provided by the Division of Image Generation (DGI) of the National Institute for Space Research (Instituto Nacional de Pesquisas Espaciais -INPE).…”
Section: Soil Cover Standardizationmentioning
confidence: 99%